The Influence Of Service Quality And Customer Satisfaction On Customer Loyalty at Bintang Supermarket - Deby Intan Dewini Gultom; Dedy Lazuardi; Isra Rafika Sihombing (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of service quality and customer satisfaction on customer loyalty, both partially and simultaneously. This study uses a quantitative approach with a survey method through a questionnaire to 110 respondents who are customers of Bintang Supermarket. The sampling technique uses accidental sampling. Data analysis was carried out using multiple linear regression with hypothesis testing through t-test and F-test, and supported by the classical assumption test and the coefficient of determination (R²). The results of the study indicate that service quality has a positive and significant effect on customer loyalty with a t-value of 5.321 greater than t-table 1.982. Customer satisfaction is also proven to have a positive and significant effect on customer loyalty with a t-value of 8.094 greater than t-table 1.982. In addition, simultaneously service quality and customer satisfaction have a positive and significant effect on customer loyalty with an F-value of 1618.843 greater than F-table 3.08. This study shows that improving service quality and customer satisfaction are important factors in creating customer loyalty at Bintang Supermarket. This research is expected to provide practical contributions to management in designing service improvement strategies and strengthening long-term relationships with customers, while also contributing theoretically to the development of marketing science, particularly in the local supermarket retail sector